LAW ENFORCEMENT AGAINST CRYPTOCURRENCY ABUSE - Untung Widyatmoko; Romli Atmasasmita; Anthon F Susanto; Bambang Heru Purwanto (International Journal Labs, 2024)
This paper aims to provide literacy or knowledge in law enforcement efforts that can be carried out against crimes by misusing cryptocurrencies as a means of transaction. This article uses a type of normative legal research using a legal perspective to produce a concept in solving problems that occur, supported by a legal approach and a case approach. The data used is sourced from secondary data with primary legal materials that are binding and fundamental. The approach method used in this study is the archival juridical approach method, which is legal research that prioritizes how to examine primary and secondary data, in the form of interviews with various sources and positive legal studies and how to implement them in practice in the field. The results of this study show that law enforcement against the misuse of cryptocurrencies requires government support in the form of clear regulations and firm legal policies on the use of cryptocurrencies. So that the law enforcement process fulfils a sense of justice for the community and the achievement of legal certainty.